2008
DOI: 10.1002/ab.20255
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity to the effects of nicotine and bupropion in adolescent and adult male OF1 mice during social interaction tests

Abstract: Few studies have compared the action of both nicotine (NIC) and bupropion (BUP), an antidepressant used to treat NIC dependence, on social and aggressive behavior at different ages. This study aims to determine whether these drugs produce differential effects in adolescent (postnatal day: 36-37) and adult (postnatal day: 65-66) mice that have been housed individually for 2 weeks in order to induce aggressive behavior. Mice received BUP (40, 20, or 10 mg/kg), NIC (1, 0.5, and 0.25 mg/kg as base), or vehicle ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
1
2
0
1
Order By: Relevance
“…This conserved action of nicotine provides strong evidence for its role as a serenic agent, as acute administration of nicotine to each strain has different locomotor consequences [22–24], and the three strains of mice differ in innate aggression levels [32] and sociability measures [19]. We also found that acute nicotine administration does not alter sociability, in agreement with previous studies in mice [28, 30, 33]. Interestingly, while acute administration of nicotine (0.25 mg/kg) to solitary B6 mice predictably reduced locomotion in both home cage and sociability apparatus environments by ~30% [22], we found that the addition of a social “stimulus” mouse rescued this locomotor deficit, providing evidence that locomotor deficits cannot fully explain the serenic effect of nicotine in our assay.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This conserved action of nicotine provides strong evidence for its role as a serenic agent, as acute administration of nicotine to each strain has different locomotor consequences [22–24], and the three strains of mice differ in innate aggression levels [32] and sociability measures [19]. We also found that acute nicotine administration does not alter sociability, in agreement with previous studies in mice [28, 30, 33]. Interestingly, while acute administration of nicotine (0.25 mg/kg) to solitary B6 mice predictably reduced locomotion in both home cage and sociability apparatus environments by ~30% [22], we found that the addition of a social “stimulus” mouse rescued this locomotor deficit, providing evidence that locomotor deficits cannot fully explain the serenic effect of nicotine in our assay.…”
Section: Discussionsupporting
confidence: 90%
“…In neutral cage encounters of socially-isolated OF1 mice with anosmic opponents, nicotine administered either acutely or chronically did not reduce aggression, whereas lobeline, a less specific nAChR agonist that also interacts with the dopamine transporter and vesicular monoamine transporter [27] reduced aggression even at doses that did not affect locomotion [28, 29]. Acute nicotine administration also did not influence sociability significantly in socially isolated OF1 mice [30]. In contrast with other studies, male albino mice administered nicotine i.p.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the current literature on mouse social behaviors consists of studies done in both phases. As shown in Table 1, while dark phase experiments continue to contribute to our current knowledge of mouse social behaviors (Arakawa et al, 2008a,b; Bluthe et al, 1993; Cheh et al, 2006; Clipperton et al, 2008; D'Amato, 1998; Daza-Losada et al, 2008; Gomez et al, 2008; Kurian et al, 2008; Leypold et al, 2002; Liu et al, 2006; McFarlane et al, 2008; McNaughton et al, 2008; Panksepp and Lahvis, 2007; Panksepp et al, 2007; Scattoni et al, 2008b; Torres et al, 2005; Yang et al, 2007b), light phase experiments have also been producing remarkable findings on genetic, neuroanatomical, and environmental factors that are important for mouse social behaviors (Babovic et al, 2008; Bielsky et al, 2004, 2005; Dluzen and Kreutzberg, 1993; Egashira et al, 2007; Ehninger et al, 2008; Fairless et al, 2008; Ferguson et al, 2001; Jamain et al, 2008; Koh et al, 2008; Lee et al, 2008; Long et al, 2004; Moretti et al, 2005; Moy et al, 2007, 2008; O'Tuathaigh et al, 2008; Refinetti, 2004; Ryan et al, 2008; Scattoni et al, 2008a; Scearce-Levie et al, 2008; Spencer et al, 2008; Stack et al, 2008; Wersinger et al, 2008; Winslow and Camacho, 1995; Wrenn et al, 2004). …”
Section: Social Behaviors Measured In a Novel Environment: Not Strongmentioning
confidence: 99%
“…En este trabajo, la provocación social, realizada treinta minutos antes del encuentro agonístico, modifica el repertorio conductual agresivo del animal aislado aumentando las conductas de amenaza y ataque e incrementando la conducta de exploración a distancia, que forman parte de la secuencia del patrón agonístico del animal que generalmente precede a la conducta agresiva; también la conducta de cuidado corporal, que es muy sensible a factores endógenos y exógenos, sugiriéndose como una conducta útil para evaluar los cambios conductuales ante situaciones estresantes (Gómez, Carrasco & Redolat, 2008), lo que podría estar apoyando la idea de que la instigación hubiese incitado en estos animales un estado de activación agresivo, que les llevaría a incrementar los niveles de agresión.…”
Section: Resultsunclassified